1969
DOI: 10.1346/ccmn.1969.0170304
|View full text |Cite
|
Sign up to set email alerts
|

Soil Minerals in the Al2O3-SiO2-H2O System and a Theory of Their Formation

Abstract: Abstract-An attempt has been made to assemble the best thermodynamic information currently available for soil minerals in the AI.203-SiO2-H._,O system at 25~ and 1 atm. Montmorillonite is included by considering its aluminum silicate phase. Diagrams are presented so that the stability of the minerals can be visualized in relation to the ionic environment. Although the AI20:~-SiO2-H20 system is a very simple one compared to soils and sediments, the stability diagrams depict a mineral stability sequence and mine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(56 citation statements)
references
References 29 publications
2
54
0
Order By: Relevance
“…Leaching of Si from the soil and plant uptake are also important in determining Si concentrations in soils (Kittrick, 1969). The concentration of soluble Si in soils is undoubtedly dynamic, where equilibrium conditions are the exception rather than the rule.…”
Section: Silicon In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Leaching of Si from the soil and plant uptake are also important in determining Si concentrations in soils (Kittrick, 1969). The concentration of soluble Si in soils is undoubtedly dynamic, where equilibrium conditions are the exception rather than the rule.…”
Section: Silicon In Soilmentioning
confidence: 99%
“…Others have suggested that amorphous Si coatings formed due to dehydration (McKeague and Cline, 1963c), kaolinite and montmorillonite (Kittrick, 1969), a surface aluminosilicate component (R) of variable composition (Weaver and Bloom, 1977), and/or opal (Wilding et al, 1979) might regulate the amount of Si in the soil solution. As monosilicic acid l oses water, it forms socalled silica gel until the proper moisture content is reached.…”
Section: Silicon In Soilmentioning
confidence: 99%
“…Energy-dispersive X-ray microanalysis (Fig. 5) (Vaughan 1978 (Lindsay 1979 (Table 8) were in the range for equilibrium solutions with smectite minerals (Kittrick 1969 …”
Section: Methodsmentioning
confidence: 99%
“…Amorphous ferrihydrite was modeled using the log K value from the SIT database, which is also included in the PhreeqC package, and the standard enthalpy of reaction (ΔH) from the LLNL database. Data for amorphous aluminum hydroxide were taken from Kittrick (1969). No ΔH values were available for amorphous aluminum hydroxide and manganese oxohydroxide, so no direct temperature dependence could be calculated for these two phases.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Data taken from the LLNL database, except log K of ferrihydrite (SIT database) and amorphous aluminum hydroxide (Kittrick 1969 …”
Section: Table 2 Dissolution Reactions Considered In the Modelmentioning
confidence: 99%